Blood Transfusion in Obstetric Cases: Transfusi Darah pada Kasus Obstetri - Ali Sungkar; Raymond Surya (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: To discuss about blood loss in an obstetric setting, the role of blood transfusion, and patient blood management.Methods: Literature review.Results: Severe anaemia with hemoglobin level less than 7 g/dL or late gestation (more than 34 weeks) and/ or significant symptoms of anaemia, the recommendation is giving only single unit transfusion followed by clinical reassessment for further transfusion. In postpartum hemorrhage (PPH), massive transfusion protocols are commonly used description as large volume of blood products over a brief period to a patient with uncontrolled or severe hemorrhage, transfusion more than 10 RBC units within 24 hours, transfusion more than 4 RBC units in 1 hour with anticipation of continued need for blood, replacement of more than 50% of total blood volume by blood products within 3 hours. All obstetric units have a clear-cut massive transfusion protocol for the initial management of life-threatening PPH, considering early transfusion therapy with RBCs and FFP.Conclusion: Patient blood management aims to maintain hemoglobin concentration, optimize haemostasis, and minimize blood loss in effort to improve patient outcomes. Massive transfusion protocol in management of life-threatening should depend on each obstetric unit.Keywords: blood transfusion, obstetric cases, patient blood management. Abstrak Tujuan: Untuk mendiskusikan tentang hilang darah dalam obstetric, peran transfusi darah, dan patient blood management.Metode: Kajian pustaka.Hasil: Anemia berat dengan nilai hemoglobin kurang dari 7 g/dL atau kehamilan lanjut (lebih dari 34 minggu) dan/ atau gejala nyata anemia, rekomendasi ialah memberikan satu unit transfusi diikuti dengan penilainan klinis untuk transfusi lebih lanjut. Pada perdarahan postpartum, protokol transfusi massif umum digambarkan sebagai volume darah yang dibutuhkan jumlah banyak dalam periode singkat, transfusi lebih dari 10 sel darah merah dalam 24 jam atau lebih dari 1 jam, penggantian lebih dari 50% total volume darah dalam 3 jam. Seluruh unit obstetric memiliki protokol transfusi massif yang jelas untuk taalaksana awal perdarahan postpartum dengan mempertimbangkan transfusi awal untuk komponen sel darah merah dan FFP.Kesimpulan: Patient blood management bertujuan untuk menjaga konsentrasi hemoglobin, optimalisasi hemostasis, dan minimalisasi hilang darah untuk meningkatkan luaran pasien. Protokol transfusi masfi dalam tatalaksana yang mengancam nyawa sangat bergantung pada setiap unit obstetrik.Kata kunci: kasus obstetri, patient blood management, transfusi darah